Process Optimization to Improve Immunosuppressant Drug Testing Turnaround Time. - Barakauskas, Vilte E.; Bradshaw, Tiffany A.; Smith, Lonnie D.; Lehman, Christopher M.; Johnson-Davis, Kamisha L. (American Journal of Clinical Pathology, 2016)
Objectives: Timely reporting of immunosuppressant (ISP) drug level results is needed for transplant patient management. This study characterized the local ISP testing process, identified bottlenecks and implemented process improvements to meet turnaround time requirements.Methods: Laboratory information time stamps, direct observation and discussion with staff were used to construct a value stream map of the ISP testing process to identify process bottlenecks. Improvements were implemented to attain the required turnaround time.Results: Baseline performance of the existing ISP process (seven weeks, n = 272 samples) indicated that only 28% of samples were reported by 2:00 pm Major bottlenecks were identified to be the analytical run schedule, instrument delays, difficulty identifying ISP samples at intake, and difficulty collecting specimens. Process changes resulted in a median of 76% samples reported by 2:00 pmConclusions: : Adjusting ISP collection and analysis processes improved the laboratory's ability to meet physician requested result reporting time of 2:00 pm.